Online Zakat Payment Intentions in Post-Fraud Exposure: The Moderating Roles of Perceived Behavioral Control and Media Literacy - Muhammad M. Hakim; Gaguk Tri Prasetyo; Mochamad Nursalim; Amrozi Khamidi; Joko Setiawan (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2025)
Zakat is a form of charity that must be done by Muslims to help those in need, but in this digital era, the emergence of online fraud has the potential to reduce trust in zakat organizers and have an impact on a person's willingness to pay zakat online. This study aimed to explore the effect of trust in fundraisers and cyber-fraud perceptions on the willingness to pay zakat online by considering the moderating variables of perceived behavioral control and media literacy. This study was a quantitative study, with a sample of 237 Muslims in Indonesia who have been victims of fraud on social media. The research data obtained through a survey mechanism from June to October 2024 were then analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of this study showed that trust in fundraisers had a significant effect on the willingness to pay zakat online when control variables such as age group, gender, education level, and marital status are considered. Without considering the control variables, this effect was not significant. On the other hand, cyber-fraud perception did not significantly affect willingness to pay zakat in both models, although there was a negative tendency. Furthermore, perceived behavioral control does not act as a moderator in the relationship between trust in fundraisers and cyber-fraud perception on willingness to pay zakat. Media literacy showed a significant moderating effect in the model without control variables in the influence between trust in fundraisers and willingness to pay zakat online.